Avaliação da esperança, ansiedade e depressão em pacientes com câncer no sistema gastrointestinal - BOSCOLO, Luana Barbosa Zago (2017)
Among the types of cancer that affect the Brazilian population the most, it is possible to note that a significant amount is in the gastrointestinal track. The disease can provoke physical, emotional and social damages, as well as difficulties due to the treatment undergone by the patient, which can be aggressive or mutilating and have several adverse effects. The clinical follow-up of these patients suggests that they present depression and anxiety symptoms since the moment of the diagnostic. The treatment can impose some difficulties and limitations, but it is possible to keep hope when one thinks about the possibility of a cure. Hope encourages the patients to keep on fighting, so they can resume life projects. The general objective of this study was to analyze the relationship between sociodemographic and clinical variables, anxiety, depression and hope of patients with cancer in the gastrointestinal tract, in the preoperatory period. To collect the data, three instruments were used: one containing sociodemographic and clinical data of the patient, the Hospital Anxiety and Depression Scale (HADS) and the Herth Hope Index. For the statistical analysis of the categoric variables, frequency distribution was used both in absolute numbers and in percentage, while for the calculation of the quantitative variables, measures of central tendency and dispersion were employed. The categoric variables were compared to the anxiety scores with Student’s T-test, and regarding the scores of depression and hope, the non-parametric Mann-Whitney test was also used. As to the quantitative variables, the correlations of Pearson and Spearman were used. 36 patients participated in the study. On average, they were 62.08 years old, of a low educational level, retired, their monthly income was from one to two minimum wages, they were married and followed a religion. Regarding clinical aspects, most patients presented colon and rectal cancer, with no metastasis and no treatments conducted before the surgery. They had been hospitalized for one day for their first surgical procedure to deal with the tumor. Generally, the patients presented low anxiety (5.41) and depression (3.13) levels with Cronbach’s alpha of 0.75 and 0.78, respectively. In the univariate analysis, it was found that the educational level influenced anxiety. Regarding depression, the patients who had partners had lower depression levels. In the multivariate analysis, however, no variable presented statistically meaningful difference. Most patients had a high level of hope, as evidenced by the average result (42.89). When the relationship between hope and the sociodemographic and clinical variables was analyzed, significant differences were identified for anxiety and depression. The less the score of anxiety and depression, the greater the score of hope. It was found that the subjects of the study, even when confronted with a surgical procedure, were calm and hopeful. Nursing, due to its close link to the patients, must help them through the recognition of signals of emotional disorders and through the promotion of hope.